Strategic Culture Cult of Defense: Dominant Culture in China's Salami Slicing Geopolitical Strategy - Paramesvari, Nyoman Sekar Ayu (JUSS (Jurnal Sosial Soedirman), 2024)
China continues to try to establish norms in international dynamics, especially in Asia, with a "salami-slicing" strategy to expand its influence without triggering major conflicts. This strategy is seen in how China responds to its two territorial disputes; the occupation of islands in the South China Sea and the Indian border. The salami-slicing strategy helps China gradually occupy disputed territories and offers a fait accompli that the other party must accept. This paper will then use Bloomfield's strategic culture framework which emphasizes the existence of dominant and subordinate subcultures. The author finds that in influencing China's policies in territorial disputes, the dominant strategic culture is the Cult of Defense coined by Scobell. This strategic culture has three (3) implications for policy, namely projecting strength when on the verge of crisis and the tendency to take risks, and in the outline of its actions, China will then justify using its power.